2017
DOI: 10.5935/0004-2749.20170002
|View full text |Cite
|
Sign up to set email alerts
|

Tear osmolarity and ocular surface parameters in patients with psoriasis

Abstract: The results of this study showed that psoriasis may influence tear osmolarity and tear film function. Patients with psoriasis showed tear hyperosmolarity and tear film dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 0 publications
2
25
0
Order By: Relevance
“…They suggested psoriasis may effect on tear osmolarity and tear film function by inflammatory processes. 20 In a study by Santos da Cruz et al with 43 psoriasis patients and 86 controls, it was found that patients with psoriasis had a statistically higher rate of dry eye (16.28%), likely dry eye (32.56%), blepharitis (16.28%), and ocular surface disease and Rose Bengal tests were more abnormal in patients with psoriasis. 21 In the present study, according to the TFOS DEWS II criteria, 24 the frequency of DED was significantly higher in patients with psoriasis (22%), which was consistent with the literature.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…They suggested psoriasis may effect on tear osmolarity and tear film function by inflammatory processes. 20 In a study by Santos da Cruz et al with 43 psoriasis patients and 86 controls, it was found that patients with psoriasis had a statistically higher rate of dry eye (16.28%), likely dry eye (32.56%), blepharitis (16.28%), and ocular surface disease and Rose Bengal tests were more abnormal in patients with psoriasis. 21 In the present study, according to the TFOS DEWS II criteria, 24 the frequency of DED was significantly higher in patients with psoriasis (22%), which was consistent with the literature.…”
Section: Discussionmentioning
confidence: 95%
“…Dry eye test abnormalities in patients with psoriasis have been shown in several studies. 19 , 20 , 21 Ghalamkarpour et al performed a study with 200 psoriatic patients and 100 healthy controls, it was found that the mean values of TBUT and Schirmer's tests in patients were significantly lower than the controls, and significantly higher scores of OSDI were observed among patients compared to the controls. Dry eye disease was observed more frequently in the patients than in the healthy group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, Celik et al [20] suggested that psoriasis affected the corneal biomechanical properties. Demirci et al [21] found out that osmolarity values, OSDI and Oxford scale scores were significantly higher and the tear film break-up time was significantly shorter in patients with psoriasis compared to the healthy controls. Some researchers evaluated the posterior segment structures of the eye in psoriasis, which had similar aspects with LP in the pathogenesis since it also involved systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%